ESBL and AmpC β-Lactamases in Clinical Strains of Escherichia coli from Serra da Estrela, Portugal - Oliveira, Cátia (2019)
Background and Objectives: Given the considerable spatial, temporal, and ecological factors, heterogeneity, which affects emergency response, persistence, and dissemination of genetic determinants that confer microorganisms their resistance to antibiotics, several authors claim that antibiotics' resistance must be perceived as an ecological problem. The aim of this study was to determine the prevalence of broad-spectrum bla genes, not only Extended-spectrum β-lactamases (ESBL) but also AmpC-types, in clinical strains of Escherichia coli isolated from Portugal (in the highest region of the country, Serra da Estrela) to disclose susceptibility profiles among different genotypes, and to compare the distribution of bla genes expressing broad-spectrum enzymes. Materials and Methods: Clinical strains of Escherichia coli presenting resistance to third generation (3G) cephalosporins and susceptibility to inhibition by clavulanic acid were studied by means of phenotypic and molecular profiling techniques for encoding β-lactamases genes. Results: Strains were mainly isolated from hospital populations (97%). Molecular analysis enabled the detection of 49 bla genes, in which 55% (27/49) were identified as blaOXA-1-like, 33% (16/49) as blaCTX-M-group-1, 10% (5/49) as blaTEM, and 2% (1/49) were identified as genes blaCIT (AmpC). Among all blaOXA-1-like detected, about 59% of strains expressed at least another bla gene. Co-production of β-lactamases was observed in 40% of strains, with the co-production of CTX-M group 1 and OXA-1-like occurring as the most frequent. Conclusions: This is the first study using microorganisms isolated from native people from the highest Portuguese mountain regions, showing an unprecedent high prevalence of genes blaOXA-1-like in this country.